Handball Training and Competition With Facemasks in Galicia: The FISICOVID-DXTGALEGO Protocols Experience - Rico-Díaz, Javier; Río-Rodríguez, Dan; Gómez-Varela, Joaquín; Martín-Acero, Rafael (Frontiers in Psychology, 2022)
Objective: COVID-19 caused a complete stop in non-professional sports. The use of face masks for team sports is not a widely used measure in non-professional sports. The study aimed to evaluate the perception about using the mask and the adaptation difficulties related to training and competition in team sports following the FISICOVID-DXTGALEGO protocol. Methods: 787 handball players from the Galician Handball Federation were followed during their return to participation after months of confinement through an electronic questionnaire of perception and experience on the use of a mask. Results: There is an excellent adaptation to the mask in training and competition with medium and high correlations. The 86,41% of players reported an adaptation to the mask in 3 weeks with a three times a week training frequency. The negative opinion on the mask was drastically reduced (-66.86%) after use. The 80,44% of players considered the use of a mask as an essential measure to resume competitions. Conclusions: It is very feasible to adapt to training and compete with a mask (hygienic or surgical) in a short period. The use of a mask following these protocols changed previous opinions on the disadvantages of the mask during training and competition